PENGARUH GAYA KEPEMIMPINAN TERHADAP MOTIVASI KERJA KARYAWAN DI PT SENTRALSARI PRIMASENTOSA CLEO CABANG TASIKMALAYA - Setiana, Adi Robith; Dea Arviyani (Journal of Innovation Research and Knowledge, 2024)
This study aims to find out: 1. How is the Leadership Style at PT Sentralsari Primasentosa Cleo Tasikmalaya Branch? 2. How is the Work Motivation of Employees at PT Sentralsari Primasentosa Cleo, Tasikmalaya Branch? 3. How does leadership style influence employee motivation at PT Sentralsari Primasentosa Cleo Tasikmalaya Branch? The research method used is a quantitative descriptive method, with the number of respondents in this study being 30 people. With the sampling technique that is carried out by total sampling / saturated sampling (sampling technique, all members of the population are sampled). The data used in this study are primary data and secondary data. The analytical tool used is simple regression analysis. The results of this study indicate that the Leadership Style Variable has a significant effect on employee motivation.